Research choice: Pragmatism in conducting research about university enterprise collaboration in the Vietnamese context (Revista Lusófona de Educação, 2017)
This article discusses the choice of methodology I had when conductingresearch on the university-enterprise collaboration (UEC) in theVietnamese context. As I am more interested in how best to addressthe research problems rather than in the politics of methodology, thediscussion in this paper will not focus on the differences between thetwo dominant approaches to educational research (qualitative andquantitative). Rather, this paper will discuss my way to approach theproblems in order to find the best possible answers for the researchquestions. In this study, pragmatic approach was employed to developa rich, contextualized understanding of underlying values, beliefs andassumptions that guide actions. This was done by a two phases researchstudy: quantitative surveys focusing primarily on revealing current UECsituation, its obstacles and solutions were used first, then the qualitativeinterviews were followed to explore in depth why those obstacles existedand how feasible the solutions were - this was also the goal of this study.The focus on the second phase – to discuss the most meaningful andrevealing issues related to the local issued of UEC, ultimately, helped meproduce more meaningful study outcomes.